Pengaruh Konsentrasi Polyaluminium Choride (PAC) dan Polydadmac Terhadap Proses Koagulasi dan Flokulasi pada Pengolahan Air Sungai Cengkareng Drain - Redjeki, Athiek Sri; Darmi, Hedro; Yudistirani, Sri Anastasia; Purnawan, Irfan; Hasyim, Ummul Habibah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
This study was conducted to determine the effect of the concentration ratio of Polyaluminium Choride (PAC) and Polydadmac coagulants on the coagulation and flocculation processes in river water treatment. The raw water used is raw water that is processed by IPA Taman Kota PT. XYZ namely Cengkareng Drain river water with a turbidity of 19.3 NTU and a pH of 7.22. This study uses the jar test method. The selected variables are variations in the concentration of PAC and polydadmac. The water produced from the jar test was tested for its turbidity and pH. This research was started by sampling raw water, then 1000 ml was put in each glass jar test tool. Then the flocculation process was carried out with a stirring speed of 200 rpm for 2 minutes. Followed by the coagulation process with a stirring speed of 40 rpm for 18 minutes. The process continued with sedimentation for 10 minutes. The optimum dose obtained was the combination of 20 ppm PAC and 0.4 ppm polydadmac with a turbidity value of 1.08 NTU or with a removal efficiency value of 94.40% and a pH value of 7.06.